2020
DOI: 10.1159/000511359
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sarcopenia and Swallowing Capacity in Community-Dwelling Older Women

Abstract: <b><i>Background:</i></b> Swallowing disorders are a serious health concern among older adults. Previous studies reported that sarcopenia may affect swallowing disorders; however, whether sarcopenia is related to the capacity to swallow (measured according to swallowing speed) in community-dwelling older adults is unclear. <b><i>Objectives:</i></b> The aim of this study was to investigate the relationship between sarcopenia and swallowing capacity in community-dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The modified water swallowing test (MWST) is a simple measurement to detect aspiration by swallowing water [42]. A total of 3 mL cold water is poured over the floor of the mouth by using a 5 mL syringe, and then the patients are instructed to swallow [43].…”
Section: Jaw-opening Force Not Availablementioning
confidence: 99%
“…The modified water swallowing test (MWST) is a simple measurement to detect aspiration by swallowing water [42]. A total of 3 mL cold water is poured over the floor of the mouth by using a 5 mL syringe, and then the patients are instructed to swallow [43].…”
Section: Jaw-opening Force Not Availablementioning
confidence: 99%
“…Tongue strength measurement has been proposed as a diagnostic tool for sarcopenic dysphagia ( 19 ). The modified water swallowing test (MWST) has been widely used by medical practitioners to screen for dysphagia ( 20 ). However, it puts the examinees at risk of choking.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the clinical importance of sarcopenia gradually increases with growing interest in the elderly's quality of life and healthcare costs 10 . Not enough research has been conducted on the association between sarcopenia and laryngeal function, which is vital for vocalisation; however, one study has reported that sarcopenia is related to the swallowing ability of older women 11 . Many factors contribute to changes in voice with age, and it has been reported that the larynx muscles, such as the thyroarytenoid (TA) muscle, play an important role 12 …”
Section: Introductionmentioning
confidence: 99%
“…10 Not enough research has been conducted on the association between sarcopenia and laryngeal function, which is vital for vocalisation; however, one study has reported that sarcopenia is related to the swallowing ability of older women. 11 Many factors contribute to changes in voice with age, and it has been reported that the larynx muscles, such as the thyroarytenoid (TA) muscle, play an important role. 12 Several muscles of the larynx, which are essential for vocalisation, are thought to be associated with appendicular skeletal muscles, like other muscles of the body.…”
Section: Introductionmentioning
confidence: 99%